The Leadership of Behice Boran in the Turkish Workers’ Party (October 1, 1970 - October 10, 1987) (A Historical Study) - Obeed, Dr.Ali Talib; Hussein, Zahraa Hashim (Thi Qar Arts Journal, 2024)
Behice  boran was the first Turkish woman to lead a political party in Turkey. Throughout her political career, she witnessed three military coups in Turkey and had different reactions to each. The year 1960 marked the actual beginning of Boran’s political journey and was also a pivotal point in Turkish history as it saw the first military coup, which allowed the formation of parties and labor unions. This led to her becoming the leader of the Turkish Workers’ Party in 1970. However, the party faced a setback following the second military coup in 1971, which differed politically from the first due to the presence of the right-wing on the political scene, restricting the leftist movement. Boran was arrested for the third time during the period (1971-1974), and she criticized this coup. She was released from prison in 1974 and managed to re-establish the party in 1975, but it was closed again following the third military coup in 1980, leading to her fourth arrest. Due to her deteriorating health, she was released and decided to leave Turkey, seeking political asylum in Belgium, where she remained in exile until her death in 1987 after spending seven years in exile.